Applicability of Period of Limitation in Rural Land Disputes: Case Comment - Ambaye, Daniel (Bahir Dar University Journal of Law, 2022)
The purpose of this case comment is to shed light on the concepts of both acquisitive and extinctive prescriptions and comment whether the court’sdecisions upheld today is really in line with the intention of the land policy that we adopt. This comment is mainly based on the different decisionsdelivered by the Federal Supreme Court Cassation Division (FSCCD) during the past several years. The ambiguous nature of the applicability of the periodof limitation principle on landholdings and the double stands that the court holds and which discriminates between private and state holdings encourageus to prepare this comment.